A simple approach to estimate long-term interest rates - Joost Driessen; Theodore E. Nijman; Zorka Simon (Leibniz Institute for Financial Research SAFE, 2022)
We propose an easy to implement yield curve extrapolation method to determine long-term interest rates suitable for regulatory valuation. We empirically evaluate this approach for the German nominal bond market, by estimating the model on bonds with maturities up to 20 years and assessing the out-of-sample performance for bonds with maturities beyond 20 years. Even though observed long-term yields are somewhat lower than the predicted yields, the method performs quite well empirically given its simplicity. We perform a case study on pension fund liability valuation and show that our proposed method would have a substantial impact on liability values.
Keywords: G01; G12; G15; G18; 330; Sovereign Bonds; Term Structure of Interest Rates; Segmentation; Liquidity; Flight-to-safety; Credit Risk